Impact of battery-powered orthopedic drills on the practice of orthopedic surgery in a resource limited country - Baidoo, Paa K.; Ocloo, Agbeko; Ansu, Velarie; Baidoo, Joojo N. (International Surgery Journal, 2018)
Background: The study aimed at assessing the impact of the availability of battery-powered drills on the management of orthopedic cases presenting to the orthopedic unit of the department of surgery at a major teaching hospital serving the southern part of Ghana. Methods: This study was a single center retrospective study. Authors examined the total number of cases, average time spent on cases in the operating room, and the average patient waiting time for surgery between January 2012 and December 2014. A paired sample t-test was used to evaluate the effectiveness of the orthopedic drills for the pre-and post-intervention periods. Results: There were statistical significant differences in the total number of cases (p<0.01), the average time spent on cases in the operating room (p<0.01), and the average waiting time for surgery (p<0.05) between January 2012 to June 2013 when manual hand drills were in use and July 2013 to December 2014 when the battery-powered drills were introduced. Conclusions: The introduction of the battery-powered drills led to a significant improvement in the total number of cases done. There was a reduction in time spent per case in the operating room as well as the average waiting time to having surgery.